ARTERIOLOSCLEROSIS IN BOVINE HEPATIC TISSUE INFESTED CHRONICALLY BY FASCIOLIASIS - A. ABDUL RAHMAN , RAJEHA (The Iraqi Journal of Veterinary Medicine, 1996)
This investigation aimed at studying the arteriolar lesions in the hepatic infestation with fascioiiasis. Specimens from slaughterhouse were collected, and studied by histopathology. Sclerotic lesion was revealed in the arteriolar walls of chronic type infestation, while mild arteriolitid was only found in the acute migratory phase.